Time-dependent Expression of Caspase-3 and Degeneration of Lateral Rectus Muscle on Experimental Esotropia in Rabbits - Luki Indriaswati; Nurwasis; Gatut Suhendro; Soetjipto; Retno Handajani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: To identify correlation between caspase-3 expression and degeneration of lateral rectus muscleon experimental esotropia in rabbits by using time dependent analysis. Methods: Twenty four rabbits weredivided into 4 groups, first month sham (S1); second month sham (S2); first month esotropia (E1); andsecond month esotropia (E2) model groups. Immunohistochemical and haematoxyllin eosin staining wereperformed. Results: In first month observation no significant difference in caspase-3 expression between S1(1.56 ± 1.03) and E1 (3.93 ± 1.66) groups (p >0.05) and in the degeneration score of lateral rectus musclebetween S1 (1.33 ± 1.36) and E1 (3.83 ± 2.04) groups (p> 0.05). In second month observation no significantdifference in caspase-3 expression between S2 (1.80 ±1.08) and E2 (6.50 ± 3.26) groups (p >0.05); butthere was significant difference in the degeneration score of lateral rectus muscle between S2 (1.16 ± 1.16)and E2 (4.50 ± 1.04) groups (p <0.05). There was a significant correlation between caspase-3 expressionand the degeneration score of lateral rectus muscle (p=0.020; r=0.471). Conclusion: On the experimentalesotropia with prolonged lateral muscle contraction in rabbits, the increasing trend of caspase-3 expressionhas a correlation with the increasing degeneration score of lateral rectus muscle.